2015
DOI: 10.1073/pnas.1511474112
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated levels of diesel range organic compounds in groundwater near Marcellus gas operations are derived from surface activities

Abstract: Hundreds of organic chemicals are used during natural gas extraction via high-volume hydraulic fracturing (HVHF). However, it is unclear whether these chemicals, injected into deep shale horizons, reach shallow groundwater aquifers and affect local water quality, either from those deep HVHF injection sites or from the surface or shallow subsurface. Here, we report detectable levels of organic compounds in shallow groundwater samples from private residential wells overlying the Marcellus Shale in northeastern P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
132
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(145 citation statements)
references
References 33 publications
(53 reference statements)
11
132
2
Order By: Relevance
“…Although the Pennsylvania Department of Environmental Protection (PA DEP) standards dictate that any flowback water must be treated to have a total dissolved solids (TDS) concentration of less than or equal to 500 mg/L, only one treatment plant in Pennsylvania has been completed for this purpose (Marcellus Center for Outreach and Research 2015). If not handled properly, this water may contaminate streams and groundwater (Rozell and Reaven 2012;Drollette et al 2015). Experience in Pennsylvania shows that safety and environmental violations are common in the industry: From 2009-2014, 4006 violations were reported by the PA DEP on 7,788 unconventional active wells (Amico et al 2015).…”
Section: Methods: Allarm's Shale Gas Volunteer Monitoring Study Desigmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the Pennsylvania Department of Environmental Protection (PA DEP) standards dictate that any flowback water must be treated to have a total dissolved solids (TDS) concentration of less than or equal to 500 mg/L, only one treatment plant in Pennsylvania has been completed for this purpose (Marcellus Center for Outreach and Research 2015). If not handled properly, this water may contaminate streams and groundwater (Rozell and Reaven 2012;Drollette et al 2015). Experience in Pennsylvania shows that safety and environmental violations are common in the industry: From 2009-2014, 4006 violations were reported by the PA DEP on 7,788 unconventional active wells (Amico et al 2015).…”
Section: Methods: Allarm's Shale Gas Volunteer Monitoring Study Desigmentioning
confidence: 99%
“…The management of large volumes of highly contaminated water may result in spills to surface water and/or movement into ground water supplies. Experience in the state has demonstrated that spills and accidents are common (NRDC 2015;Amico et al 2015;Drollette et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Pennsylvania the rate is more variable ranging from 0.4 spills of these materials per 100 hydraulically fractured wells to 12.2 spills per 100 wells. We choose to focus on surface spills as neither Osborn et al (2011), Drollette et al (2015 nor Manning (2015) could find cases where any underground leakages had contaminated drinking water wells. As noted in U.S. Environmental Protection Agency (2015) these contaminations do occasionally happen, but it is rare enough that it is difficult to find any rates of contamination.…”
Section: Economic Effects Of Surface Spills On Private Drinking Watermentioning
confidence: 99%
“…According to Drollette et al (2015) it is these surface spills that often result in contamination of private drinking water wells in their study area in Pennsylvania. Their careful and exhaustive study matched reported hydraulic fracturing related environmental health violations to each of their study's private drinking water well sites, and using chemical signature analysis ruled out most other non-spill related sources.…”
Section: Economic Effects Of Surface Spills On Private Drinking Watermentioning
confidence: 99%
“…Groundwater contamination can also occur from surface activities (Drollette et al, 2015;US EPA, 2015) related to shale gas production. For example, in a study evaluating groundwater contamination in the Marcellus Shale, a compound identified in flowback [water], 2-n-Butoxyethanol, was positively identified in nearby drinking water wells (Llewellyn et al, 2015).…”
Section: Groundwater Concerns During Shale Gas Developmentmentioning
confidence: 99%